2021
DOI: 10.1371/journal.pone.0254999
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the survival times of the COVID-19 patients with a new statistical model: A case study from China

Abstract: Over the past few months, the spread of the current COVID-19 epidemic has caused tremendous damage worldwide, and unstable many countries economically. Detailed scientific analysis of this event is currently underway to come. However, it is very important to have the right facts and figures to take all possible actions that are needed to avoid COVID-19. In the practice and application of big data sciences, it is always of interest to provide the best description of the data under consideration. The recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Numerous efforts have been made on solving the problem of mode mixing and thus EEMD is one such alternative approach (8). This method has the flexibility to handle very complex signals without the mode mixing problem.…”
Section: Ensemble Empirical Mode Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous efforts have been made on solving the problem of mode mixing and thus EEMD is one such alternative approach (8). This method has the flexibility to handle very complex signals without the mode mixing problem.…”
Section: Ensemble Empirical Mode Decompositionmentioning
confidence: 99%
“…In recent times, the prediction of the current pandemic of COVID-19 outbreak is a test for data experts as inadequate information is available on the initial growing curve, and the epidemiological properties of the virus to be fully elucidated. There has been a renewed interest in using time series models to predict the epidemics, namely, SARS, Ebola, influenza, and dengue (3)(4)(5)(6)(7)(8)(9)(10). These studies have shown an increasing curiosity in applying time series models as valuable tools in estimating and predicting epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, we blended existing distributions together to create the new distribution. For more information, see [1][2][3][4][5][6][7][8][9]. One of the primary objectives of statistics is to develop applicable statistical models for occurrences in the real world that can be modelled using already existing probability distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Babtain et al [24] analysis the Covid-19 spread in KSA. For more studied about COVID-19 see [34] , [35] , [22] , [14] , [18] .…”
Section: Introductionmentioning
confidence: 99%